2018
DOI: 10.1111/ejn.14090
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of young donor age dopaminergic grafts in a GDNF‐loaded collagen hydrogel further increases their survival, reinnervation, and functional efficacy after intrastriatal transplantation in hemi‐Parkinsonian rats

Abstract: Biomaterials have been shown to significantly improve the outcome of cellular reparative approaches for Parkinson's disease in experimental studies because of their ability to provide transplanted cells with a supportive microenvironment and shielding from the host immune system. However, given that the margin for improvement in such reparative therapies is considerable, further studies are required to fully investigate and harness the potential of biomaterials in this context. Given that several recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 42 publications
0
48
1
Order By: Relevance
“…A further challenge for the field has been graft integration, with numerous studies observing that human PSC‐derived dopamine transplants show notably poorer striatal innervation than their human VM fetal counterparts, with a recent direct comparative study reporting a fourfold reduction within the target dorsolateral striatum (Grealish et al ., ). While a variety of trophic cues, namely, glial cell line‐derived neurotrophic factor (GDNF), have been demonstrated to improve the survival and plasticity of fetal tissue grafts, their potential for PSC‐derived grafts are only just beginning to be realized (Moriarty et al , ). Moving forwards, in addition to the identification of trophic cues capable of supporting survival and plasticity of human PSC‐derived grafts, will be the need for safe and efficient delivery approaches that are both spatially and temporally relevant to the duration of graft integration.…”
Section: Cell Replacement Therapy For Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A further challenge for the field has been graft integration, with numerous studies observing that human PSC‐derived dopamine transplants show notably poorer striatal innervation than their human VM fetal counterparts, with a recent direct comparative study reporting a fourfold reduction within the target dorsolateral striatum (Grealish et al ., ). While a variety of trophic cues, namely, glial cell line‐derived neurotrophic factor (GDNF), have been demonstrated to improve the survival and plasticity of fetal tissue grafts, their potential for PSC‐derived grafts are only just beginning to be realized (Moriarty et al , ). Moving forwards, in addition to the identification of trophic cues capable of supporting survival and plasticity of human PSC‐derived grafts, will be the need for safe and efficient delivery approaches that are both spatially and temporally relevant to the duration of graft integration.…”
Section: Cell Replacement Therapy For Parkinson's Diseasementioning
confidence: 99%
“…Numerous groups have fabricated a variety of hydrogel-based biomaterials targeted at modelling the native 3D neural environment, repeatedly demonstrating that neural progenitors/neurons cultured on these scaffolds adopt more in vivo-like morphologies, differentiate and survive longer than those cultured on conventionally coated culture-ware. Many of these biocompatible scaffolds have also been shown to enhance survival and integration of transplanted neural progenitors (Rodriguez et al, 2012;Moriarty et al, 2018a).…”
Section: Figurementioning
confidence: 99%
“…Hence, the delivery of cells in a biomaterial matrix to which they can adhere may provide them with the necessary support needed both during and after transplantation. Indeed, studies have shown that the attachment of neural cells to biomaterials scaffolds (particularly compressive biosynthetic materials) prior to transplantation can provide cells with an adherent surface throughout the transplantation process, therefore reducing the detrimental effects of anoikis on cell survival (Béduer et al., ; Jgamadze et al., ; Moriarty, Cabre, Alamilla, Pandit, & Dowd, ; Moriarty & Dowd, ; Moriarty, Pandit, & Dowd, ; Newland et al., ).…”
Section: Cellular Brain Repair For Parkinson's Disease – Potential Ofmentioning
confidence: 99%
“…Finally, Moriarty et al. (, ) demonstrated that encapsulating VM grafts in a GDNF‐loaded collagen hydrogel resulted in a dramatic increase in the survival of dopaminergic neurons and that this correlated with enhanced striatal reinnervation and restoration of motor function in hemiparkinsonian rats.…”
Section: Cellular Brain Repair For Parkinson's Disease – Potential Ofmentioning
confidence: 99%
See 1 more Smart Citation